Circular economy in corporate sustainability reporting: a review of organisational approaches - Opferkuch, Katelin (2021)
A growing commitment from companies to implement circular economy (CE) strategies demands the development of guidelines for consistent related external communication. The fields of non-financial reporting and sustainability are well established with numerous available international reporting frameworks and approaches; however, there is still an absence of standardised reporting principles and procedures for publishing progress on circularity. In this context, this article aims to explore how companies could include CE within their corporate sustainability reports, through an academic literature review and content analysis of existent reporting approaches. Results showed a clear disconnection between CE and sustainability reporting literature. Overall, only a few of the revised reporting approaches explicitly mention CE, and the guidance given to companies is very general, inconsistent and places the responsibility of selecting performance assessment approaches on the companies. The analysis contributes to identifying opportunities for transparent external communication of CE issues, as well as exploring the challenges and limitations.